2018
DOI: 10.1111/jgh.14309
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sarcopenia on the risk of advanced colorectal neoplasia

Abstract: Our findings indicate that sarcopenia is significantly and progressively associated with the risk of advanced colorectal neoplasia. This association might be explained by metabolic factors that could be potential mediators of the effect of sarcopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…Furthermore, other previous studies have demonstrated that sarcopenia is associated with adverse postoperative outcomes and poor overall survival in patients with CRC . In addition, the presence of patients with sarcopenia is inversely related to the expense of hospital care, and is associated with advanced colorectal neoplasia and increased postoperative inflammatory response in patients with CRC .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other previous studies have demonstrated that sarcopenia is associated with adverse postoperative outcomes and poor overall survival in patients with CRC . In addition, the presence of patients with sarcopenia is inversely related to the expense of hospital care, and is associated with advanced colorectal neoplasia and increased postoperative inflammatory response in patients with CRC .…”
Section: Discussionmentioning
confidence: 99%
“…[16] In another study in which muscle mass measured by BIA in adults aged ≥50 years was corrected by weight, and sarcopenia was categorized into classes I and II according to severity, class I sarcopenia increased the risk for developing advanced colorectal neoplasia (adenoma >1 cm in size, any adenoma containing a villous component, high-grade dysplasia, or invasive colorectal cancer) by 1.14 and 1.5 times compared to class II sarcopenia. [17]…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, visceral adipose tissue may serve as a more accurate marker than the waist circumference for assessing increased CRC risk. Comparing participants with sarcopenia to those without sarcopenia, the odds ratio (95% confidence interval) was found to be 1.99 (1.63-2.43) for advanced CRC patients [16]. Lieffers et al [13] reported that sarcopenia is associated with postoperative infections and inpatient rehabilitation care, consequently resulting in a prolonged hospital stay.…”
Section: Discussionmentioning
confidence: 99%